Identification of subsurface layers and shoreline shifts in abrasion-prone areas of the northern part of Bengkulu Province using multichannel analysis surface wave method and Google Earth Pro - Sinaga, Yuni Karisma; Refrizon, Refrizon; Farid, Mochammad; Putri, Adinda Permata; Syah, Muhammad Taufiqurrahman; Sasabela, Naela Sahada (Universitas Sultan Ageng Tirtayasa, 2025)
Shoreline change is a phenomenon that occurs due to land erosion or abrasion. This study aims to measure and analyze shoreline changes and determine rock stratigraphy based on the value of secondary wave propagation velocity (Vs) in the Northern Bengkulu Province. The research was conducted at 52 points along the coast with three main stages, namely seismic data acquisition in the field, dispersion analysis, and dispersion curve inversion. Observation of shoreline changes was conducted using quantitative methods with a geophysical approach, utilizing satellite data from Google Earth Pro. Meanwhile, stratigraphic acquisition was performed using the Multichannel Analysis of Surface Waves (MASW) method. The results showed that the soil layers in the Northern Bengkulu Province area include alluvium and poor consistency, soft layers. The second to fourth layer contains a medium-dense soil layer of coarse and fine-grain soil. The fifth layer comprises a soft rock layer consisting of coarse-grain and fine-grain soils. The Vs30 values obtained range from 115 m/s to 576 m/s, indicating that the Northern part Bengkulu Province area is dominated by Site Class SC (hard, highly compacted soil and soft rock) vulnerable to deformation, including abrasion. The research results obtained in the form of Vs30 values of 115 m/s to 576m/s are dominated by three rock formations: bintunan formation, lake deposits and andesite. Stratigraphic data and Vs30 values can be used for coastal infrastructure development, such as sea walls, breakwaters, and other protection structures to reduce abrasion.